СИСТЕМАТИЗАЦИЯ ГЕРОЕ В В ПАМЯТНИКЕ «ЧАУРАСИ ВЭЙШНАВАН К И ВАРТА» - Мухибова, У. У. (Journal of Oriental Studies, 2016)
Bhukti doctrine has united many people in their way to God comprehension. The real pattern of it was saint person’s life in “The Biography of 84 saint vishnusts”. Their activity behaviour,“Bhucty doctrine’s requirements realization were actual not only for medieval India but for the present